Breastfeeding rates are high in a prenatal community support program targeting vulnerable women and offering enhanced postnatal lactation support: a prospective cohort study - Jane Francis; Alison Mildon; Stacia Stewart; Bronwyn Underhill; Samantha Ismail; Erica Di Ruggiero; Valerie Tarasuk; Daniel W. Sellen; Deborah L. O'Connor (BMC, 2021)
Abstract Background In Canada, 91% of all mothers initiate breastfeeding, but 40-50% stop by 6 months and only 34% breastfeed exclusively for 6 months, with lower rates among socially and/or economically vulnerable women. The Canada Prenatal Nutrition Program (CPNP) aims to support breastfeeding among vulnerable women, but there is no formal framework or funding for sites to integrate proactive postnatal breastfeeding support. This research aimed to i) describe infant feeding practices among clients of one Toronto CPNP site using charitable funds to offer a lactation support program (in-home lactation consultant visits, breast pumps); ii) determine whether breastfeeding outcomes at 6 months differ based on maternal sociodemographics and food insecurity; and iii) assess utilization of the lactation support program. Methods Infant feeding practices were collected prospectively at 2 weeks, 2, 4 and 6 months postpartum via telephone questionnaires (n = 199). Maternal sociodemographics were collected at 2 weeks and food insecurity data at 6 months postpartum. Program monitoring records were used to determine utilization of the lactation support program. Results Ninety-one percent of participants were born outside of Canada; 55% had incomes below the Low-Income Cut-Off; and 55% reported food insecurity. All participants initiated breastfeeding, 84% continued for 6 months and 16% exclusively breastfed for 6 months. Among breastfed infants, ≥76% received vitamin D supplementation. Approximately 50% of infants were introduced to solids before 6 months. Only high school education or less and food insecurity were associated with lower breastfeeding rates. Overall, 75% of participants received at least one visit with a lactation consultant and 95% of these received a breast pump. Conclusions This study provides initial evidence that postnatal lactation support can be delivered within a CPNP site, with high uptake by clients. While all participants initiated breastfeeding and 84% continued for 6 months, adherence to the recommended 6 months of exclusive breastfeeding was low. Further research is needed to better understand the barriers to exclusive breastfeeding and how to support this practice among vulnerable women. Study registered at clinicaltrials.gov as NCT03400605 .